Low 25-Hydroxyvitamin D Levels Are Associated With Residual Dizziness After Successful Treatment of Benign Paroxysmal Positional Vertigo - Wu, Yunqin; Han, Kun; Han, Weiwei; Fan, Zhenyi; Zhou, Min; Lu, Xiaoxiong; Liu, Xiaoxia; Li, Li; Du, Liwen (Frontiers in Neurology, 2022)
Objective: Vitamin D (Vit D) regulates calcium and phosphate metabolism and helps to maintain otolith organ function. Residual dizziness (RD) is one of the most common complications after the successful treatment of benign paroxysmal positional vertigo (BPPV). Various theories have been suggested to explain the cause of RD, and otolith organ disorder is the most evident cause of RD. This study aimed to investigate the association between serum levels of Vit D and the occurrence of RD after the successful treatment of BPPV. Methods A prospective study including patients who were diagnosed with de novo posterior semicircular canal-type BPPV (PC-BPPV) was conducted at our institution from May 2017 to May 2019. All the patients underwent canalith repositioning procedures and were followed up. Univariate and multivariate analyses were performed to investigate the relationship between serum 25-hydroxy vitamin D (25(OH)D) levels and RD occurrence after successful BPPV treatment. Results In total, 123 patients with PC-BPPV were enrolled, and 41.5% (51/123) experienced RD. The serum level of 25(OH)D was significantly lower in PC-BPPV patients with RD [median 16.2 ng/ml (IQR 12.9–22.1)] than in patients without RD [median 20.5 ng/ml (IQR 16.5–26.5)] (P = 0.001). In multivariate models comparing the prevalence of RD in the insufficient group [25(OH)D ≥ 20 to <30 ng/ml], deficient group [25(OH)D < 20 ng/ml] and normal group [25(OH)D ≥ 30 ng/ml], the 25(OH)D levels in the deficient group were associated with the occurrence of RD (odds ratio = 5.48, 95% confidence interval = 1.08–27.71; P = 0.04). Conclusion Low 25(OH)D levels are associated with the development of RD in patients with PC-BPPV after successful treatment. Further efforts to validate and elucidate the mechanism are needed.